1987
DOI: 10.1088/0264-9381/4/1/003
|View full text |Cite
|
Sign up to set email alerts
|

A Newtonian cosmology based on a Yukawa-type potential

Abstract: Within the framework of Newtonian cosmology we discuss the possible implication of a Yukawa-type gravitational interaction. In an infinite universe no effect is found and the equations of motion are the same as those for the Friedmann-Robertson-Walker models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Possible cosmological implications of new long‐range gravitational interactions have been discussed within the framework of Newtonian cosmology. D'Olivo & Ryan (1987) showed that for a homogeneous, isotropic universe, with a Yukawa‐type term in the gravitational interaction, a Newtonian cosmology exists and the equations of motions are the same as for the ordinary Newtonian case, i.e. the Friedmann equations.…”
Section: Modified Cosmic Expansionmentioning
confidence: 99%
“…Possible cosmological implications of new long‐range gravitational interactions have been discussed within the framework of Newtonian cosmology. D'Olivo & Ryan (1987) showed that for a homogeneous, isotropic universe, with a Yukawa‐type term in the gravitational interaction, a Newtonian cosmology exists and the equations of motions are the same as for the ordinary Newtonian case, i.e. the Friedmann equations.…”
Section: Modified Cosmic Expansionmentioning
confidence: 99%
“…Extensions of this approach can be found in Ref. [5]. Moreover, the same equation can be obtained even from Newton's second law [6].…”
Section: Introductionmentioning
confidence: 88%
“…( 13) with the Poisson structure from Eq. (5). By taking Θ ij = ǫ ij3 Θ one gets to the equations of motion…”
Section: Noncommutative Casementioning
confidence: 99%
“…Similarly, indications of anomalous longrange accelerations that have been found during data analysis of Pioneer 10/11, Galileo, and Ulysses spacecrafts that they are now almost outside of the solar system, made these Yukawa corrections come into play (Anderson et al 1998). In Celestial Mechanics, a Yukawa-type potential is very often proposed to modify the Newtonian one (see, e.g., D'Olivo and Ryan 1987;Iorio 2002;Brownstein and Moffat 2006;). …”
Section: Introductionmentioning
confidence: 99%